The Role of the Principal in Supporting Teachers' Duties at Wailatu Kindergarten, Olas Hamlet, Huamual District, West Seram Regency - Papalia, Diah Pratiwi; Abarua, Hermelina; Kundre, Junita Liliana; Sahetapy, Lisa Maarce (Universitas Pattimura, 2025)
This study aims to describe the role of the principal in supporting teachers' duties at TK Wailatu, Olas Hamlet, Huamual District, West Seram Regency. Using a descriptive qualitative approach, the study focuses on seven roles of the principal: educator, manager, administrator, supervisor, leader, innovator, and motivator. The findings show that the principal is key in guiding teachers, managing administration, and creating a collaborative work environment. Challenges such as low teacher competence, limited facilities, and lack of training are addressed through informal coaching strategies, local materials as learning media, access to online learning resources, and inter-school collaboration. The principal's participatory and communicative leadership style encourages teachers to remain motivated and creative. In conclusion, the principal is strategically essential in improving the quality of learning and teacher professionalism, especially in early childhood education units in remote areas. These findings are relevant for developing adaptive and context-sensitive early childhood education policies and practices